A Capabilities Framework for Dynamic Competition: Assessing the Relative Chances of Incumbents, Start-Ups, and Diversifying Entrants. (February 2023) - Murmann, Johann Peter; Vogt, Fabian
ABSTRACT: This essay argues that to assess the likelihood that incumbent firms will successfully make the required transformations to their strategy and operations in the face of technological transformations, it is not sufficient to investigate their dynamic capabilities. Whether an incumbent is likely to succeed in its effort to change itself via dynamic capabilities depends also on how quickly start-ups or diversifying entrants can build ordinary capabilities to offer the new technology at scale. We offer a framework to assess dynamic competition that integrates both ordinary and dynamic capabilities into the analysis by systematically comparing incumbents, start-ups, and diversifying entrants. We illustrate the framework with a case study of electric vehicles and aim to show how crucial such comparative analyses are for making well-founded predictions about the likelihood that incumbents will be able to maintain their leadership positions in the future.